2010
DOI: 10.1586/eri.10.28
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficileinfection: update on emerging antibiotic treatment options and antibiotic resistance

Abstract: Clostridium difficile infection (CDI) is the most common cause of identifiable diarrhea in hospitalized patients. The incidence and severity of CDIs are increasing. The increased incidence and severity of the disease has sparked interest in the optimal treatment of CDI as well as the use of new therapies and drug discovery. Current treatment strategies are inadequate with decreased response rates to metronidazole, and high recurrence rates with the use of metronidazole and oral vancomycin. Although incidence r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
70
2
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 45 publications
3
70
2
1
Order By: Relevance
“…This result is consistent with observations by BÅVERUD (2002), who reported that beta-lactams are commonly associated with CDI in foals and adult horses. In contrast to reports in other countries (HUANG et al, 2009, SHAH et al, 2010, none of the human isolates were resistant to penicillin in this study, and only one of the 13 strains tested (7.7%) was moderately susceptible to this compound.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This result is consistent with observations by BÅVERUD (2002), who reported that beta-lactams are commonly associated with CDI in foals and adult horses. In contrast to reports in other countries (HUANG et al, 2009, SHAH et al, 2010, none of the human isolates were resistant to penicillin in this study, and only one of the 13 strains tested (7.7%) was moderately susceptible to this compound.…”
Section: Discussioncontrasting
confidence: 99%
“…In general, a large variation in the MIC values were observed for tetracycline, what has also been reported in studies with C. diffi cile strains isolated from pigs and humans (DELMÉE & AVESANI, 1988;POST & SONGER, 2004;SHAH et al, 2010). However, almost all isolates from the earlier studies were susceptible to this antimicrobial.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…In a study by Baines et al (3), 24% of C. difficile 001 ribotypes demonstrated reduced susceptibility to metronidazole, which may raise questions regarding the use of metronidazole to treat very refractory cases (3). The increased rate of disease recurrence has driven the search for alternative treatments, and antibiotics such as rifaximin, nitazoxanide, tigecycline, and fidaxomicin (OPT-80) are currently being proposed as different therapies with various degrees of success (31). In addition, bacteriocins have been suggested as substitute or adjunct therapies to conventional antibiotics (4,(25)(26)(27).…”
mentioning
confidence: 99%